The Influence of Application Quality, User Experience, and Digital Promotion on the Decision to Subscribe to Spotify Premium in Indonesia - Clarissa Helga Liftiana; Haunan Damar; Guruh Taufan Hariyadi; Elia Resha Fatmawati (Golden Ratio of Mapping Idea and Literature Format, 2026)
The subscription economy model, which has become increasingly dominant amid digital disruption, positions subscription-based services as a primary revenue source for digital companies, while converting free (freemium) users into paying subscribers remains a strategic challenge. This study employed purposive sampling, a survey method, and a quantitative approach targeting active Spotify users in Indonesia. Data was analyzed using PLS-SEM to examine the relationships among variables. The results indicate that User Experience has a positive and significant effect on Subscription Decision, with a path coefficient of 0.637 and a p-value < 0.05, making it the most dominant variable influencing subscription decisions. Meanwhile, Application Quality and Digital Promotion have positive but insignificant effects on Subscription Decision. These findings suggest that the decision to subscribe to Spotify Premium is more strongly influenced by direct user experience encompassing cognitive, emotional, and functional aspects than by perceived application quality or exposure to digital promotions. The practical implication of this study highlights the importance of delivering superior user experience as a primary strategy to increase subscription decisions in digital application-based services.